Short vs prolonged dual antiplatelet treatment upon endovascular stenting of peripheral arteries - Kronlage, Mariya; Wassmann, Maximilian; Heilmeier, Britta; Müller, Oliver J.; Blessing, Erwin; Katus, Hugo; Erbel, Christian (Drug design, development and therapy, 2017)
Introduction: Peripheral artery disease (PAD) is a highly prevalent disorder with a substantial economical burden. Dual antiplatelet treatment (DAPT) upon endovascular stenting to prevent acute thrombotic reocclusions is an universally accepted practice for postinterventional management of PAD patients. However, the optimal period of time for DAPT upon endovascular stenting is not known. Methods: In the current nonrandomized, retrospective monocentric study, we evaluated the duration of DAPT upon endovascular stenting. A total of 261 endovascular SFA and iliac stenting procedures were performed on 214 patients and these patients were subdivided into a short (4-6 weeks) or a prolonged (8-12 weeks) DAPT regime group. More than 65% of the patients included were male, approximately 35% were diabetic, and 61% had a history of smoking. Of all the patients, 90% exhibited a Rutherford stage 2-3, and approximately half of the patients had a moderate-to-severe calcified target lesion with a length of >13 cm. Major safety end points were defined as any bleeding, compartment syndrome, and ischemic events. In addition to this, patency, all-cause mortality, as well as amputation were followed up over a period of 12 months upon intervention. Results: Twelve months after endovascular stenting, primary patency in our cohort was comparable between the groups (83.94% short vs 79.8% long DAPT, P>0.05). Major bleeding occurred in 18 cases without any difference between the groups (P>0.05). In addition, during the 12-month follow-up, 6 (3.4%) patients in the short and 3 (3.5%) in the prolonged DAPT regime suffered a stroke/transient ischemic attack (P>0.05). In addition, there was no difference regarding mortality and amputation rate comparing short vs prolonged DAPT regime in a 12-month follow-up. Conclusion: In the current cohort, prolonged DAPT after endovascular stenting had no beneficial effect on the outcome in a 12-month follow-up. Keywords: peripheral artery disease, stent implantation, dual antiplatelet therapy, primary patency, endovascular therapy